The exoribonuclease Xrn1 is a post-transcriptional negative regulator of autophagy - Delorme-Axford, Elizabeth (Autophagy, 2018)
Macroautophagy/autophagy is a conserved catabolic process that promotes survival during stress. Autophagic dysfunction is associated with pathologies such as cancer and neurodegenerative diseases. Thus, autophagy must be strictly modulated at multiple levels (transcriptional, post-transcriptional, translational and post-translational) to prevent deregulation. Relatively little is known about the post-transcriptional control of autophagy. Here we report that the exoribonuclease Xrn1/XRN1 functions as a negative autophagy factor in the yeast Saccharomyces cerevisiae and in mammalian cells. In yeast, chromosomal deletion of XRN1 enhances autophagy and the frequency of autophagosome formation. Loss of Xrn1 results in the upregulation of autophagy-related (ATG) transcripts under nutrient-replete conditions, and this effect is dependent on the ribonuclease activity of Xrn1. Xrn1 expression is regulated by the yeast transcription factor Ash1 in rich conditions. In mammalian cells, siRNA depletion of XRN1 enhances autophagy and the replication of 2 picornaviruses. This work provides insight into the role of the RNA decay factor Xrn1/XRN1 as a post-transcriptional regulator of autophagy.